2020
DOI: 10.21203/rs.3.rs-31313/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiating novel coronavirus pneumonia from general pneumonia based on machine learning

Abstract: Background: Chest CT screening as supplementary means is crucial in diagnosing novel coronavirus pneumonia (COVID-19) with high sensitivity and popularity. Machine learning was adept in discovering intricate structures from CT images and achieved expert-level performance in medical image analysis. Methods: An integrated machine learning framework on chest CT images for differentiating COVID-19 from general pneumonia (GP) was developed and validated. Seventy-three confirmed COVID-19 cases were consecutively enr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Abraham et al [ 26 ] combined multiple CNN-extracted features with a correlation-based feature selection (CFS) technique and a Bayesian classifier for COVID-19 prediction. Liu et al [ 27 ] developed and validated a complete machine learning framework for chest CT images to distinguish COVID-19 from global pneumonia (GP). Tuncer et al [ 28 ] proposed a novel intelligent computer vision method for automatic detection of the COVID-19 virus and conducted 10-fold cross-validation based on the SVM classifier, which showed a classification accuracy of 100.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Abraham et al [ 26 ] combined multiple CNN-extracted features with a correlation-based feature selection (CFS) technique and a Bayesian classifier for COVID-19 prediction. Liu et al [ 27 ] developed and validated a complete machine learning framework for chest CT images to distinguish COVID-19 from global pneumonia (GP). Tuncer et al [ 28 ] proposed a novel intelligent computer vision method for automatic detection of the COVID-19 virus and conducted 10-fold cross-validation based on the SVM classifier, which showed a classification accuracy of 100.0%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a convolutional neural network was used to distinguish between pneumonia patients and healthy controls [30]. Besides, novel coronavirus pneumonia was differentiated from general pneumonia using the convolutional neural network [31]. Moreover, a variety of deep learning feature embedding methods were used to improve the recognition accuracy of COVID-19 pneumonia [32], screen diseased frames from pneumonia images [33], and screen patients with pneumonia [34].…”
Section: Discussionmentioning
confidence: 99%
“…In studies of adults with COVID‐19, lung imaging quantification has been successfully implemented to predict adverse outcomes and severe complications 13–16 . We previously described CXR‐based methods to quantify lung disease severity in pediatric viral LRTIs 19–23 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that 64% of lung CT images in PCR‐confirmed pediatric COVID‐19 cases had abnormalities, primarily characterized by focal ground‐glass opacities (GGO) and consolidations 2 . In adult COVID‐19 cases, CT scan‐based algorithms have recently been developed for lung disease quantification and prediction of life‐threatening complications 13–16 . However, chest CT‐based risk prediction approaches cannot be readily applied to infants and children due to concerns about sedation requirements, radiation exposure, and costs 17,18 .…”
Section: Introductionmentioning
confidence: 99%